银杏叶提取物注射液治疗后循环缺血性眩晕疗效的meta分析 Meta-analysis of the Efficacy of Ginkgo Biloba Extract Injection in Posterior Circulation Ischemia Vertigo - 平曼1，潘培炎2，米东华2 (Zhongguo cuzhong zazhi, 2023)
目的 系统评价银杏叶提取物注射液治疗后循环缺血性眩晕（posterior circulation ischemia vertigo，PCIV）的有效性及安全性。 方法 检索中国知网、万方、维普、PubMed、EMbase和Cochrane Library等数据库，检索时限均为自建库至2022年7月，纳入银杏叶提取物注射液治疗PCIV的随机对照试验（randomized controlled trial，RCT），试验组为银杏叶提取物注射液，对照组为临床常用抗眩晕药物。利用Cochrane协作网偏倚风险工具评价纳入研究的方法学质量。使用ＲevMan 5.4.3软件对试验组和对照组治疗PCIV的临床总有效率、治疗后脑血流速度、血液黏度指标等进行meta分析。 结果 共纳入16项RCT，1545例患者（试验组785例，对照组760例）。meta分析表明，试验组的临床总有效率（OR 4.03，95%CI 2.90～5.61，P<0.001）高于对照组；左椎动脉平均血流速度[加权平均差（weighted mean difference，WMD）4.81，95%CI 2.91～6.71，P<0.001]、右椎动脉平均血流速度（WMD 4.70，95%CI 2.80～6.60，P<0.001）、基底动脉平均血流速度（WMD 5.05，95%CI 3.07～7.03，P＜0.001）等指标均优于对照组。 结论 银杏叶提取物注射液能够改善PCIV的临床疗效，且能有效改善椎基底动脉的血流速度。 Abstract: Objective To evaluate the clinical efficacy and safety of ginkgo biloba extract injection in posterior circulation ischemia vertigo (PCIV). Methods Primariy studies were systematically searched from the databases of CNKI, WanFang, VIP, PubMed, Embase and Cochrane Library published before July 2022. Randomed controlled trials (RCTs) reporting efficacy of ginkgo biloba extract injection in treatment of PCIV were included, the experimental group was ginkgo biloba extract injection, and the control group was anti-vertigo drugs. The Cochrane Collaboration bias risk assessment tool was used to measure the methodological quality of included studies. The meta-analysis was performed using the program RevMan 5.4.3 to analysis the difference of clinical total effective rate, cerebral blood flow velocity after treatment and blood viscosity index between the experimental group and control group. Results A total of 16 RCTs were finally included, involving 1545 patients (785 patients in experimental group and 760 patients in control group. Meta-analysis showed that the clinical total effective rate (OR 4.03, 95%CI 2.90-5.61, P<0.001), the left vertebral artery flow velocity[weighted mean difference (WMD) 4.81, 95%CI 2.91-6.71, P<0.001], the right vertebral artery flow velocity (WMD 4.70, 95%CI 2.80-6.60, P<0.001) and the basilar artery flow velocity (WMD 5.05, 95%CI 3.07-7.03, P<0.001) in the experimental group were all better than those in the control group. Conclusions Ginkgo biloba extract injection could improve the clinical efficacy of PCIV, and could improve the blood flow velocity of vertebrobasilar artery.